Correlation between associating factors of obstructive airway disease with obstructive sleep apnoea - ., Samta; Surynarayana, H. V.; Chandrashekhar, H. B.; H. L., Prasad (International Journal of Research in Medical Sciences, 2017)
Background: Several researchers reported that OSA may contribute to asthma symptoms and severity. But, the relation between associating factors of obstructive airway disease with obstructive sleep apnoea was not well documented. Therefore, the present study has been undertaken to investigate the relation between associating factors of OAD with obstructive sleep apnoea. Methods: Pulmonary Function Test was done for assessing air flows and measuring absolute and predicted values of FEV1, FVC, FEV1/FVC and MMEF. PFT was interpreted as normal if FEV1/FVC >70 as per GOLD and >75 as per GINA, with normal FEV1 and normal FVC. Decreased FEV1, Decreased FVC, Decreased FEV1/ FVC, predicted (<70 as per GOLD and <75 as per GINA was considered obstructive disorder. FEV1 used to follow severity in COPD. Decreased FEV1, Decreased FVC, FEV1/FVC normal or increased was considered restrictive disorder. The data were represented as percentages and mean + SD. Chi-square test and student‘t’ test was used to determine the statistical difference and a “p” value of less than 0.05 was considered the level of significance. Results: The sleep efficiency, oxygen saturation, mean heart rate, arousal index and respiratory distress index in the OAD group and in the No OAD group was found to be statistically not significant (p>0.05). The Sleep Stages in the study group (OAD and No OAD group) was also statistically insignificant except for Stage III. The PFT-FEV1was found to be statistically significant (p=0.043) when compared between OAD group and in the No OAD group. Conclusions: Due to the consequences of the overlap syndrome, it is recommended to actively search for existence of OSA, and to treat it with continuous positive airway pressure (CPAP) concurrently with oxygen and optimal pharmacological treatment.